Evaluation of Clinical Efficacy and Patient Compliance of Interdental Floss as an Adjunct to Toothbrushing for Control of Dental Plaque: A Comparative Study - Sanyukta Rajesh Chipre; Monali Shah (Journal of Integrated Health Sciences)
Introduction: Good oral hygiene is vital for overall health, and interdental floss is a key tool for maintaining a healthy mouth by removing plaque and food particles from between teeth. However, the success of floss depends on patient compliance, which is crucial for its effectiveness. The aim of this study was to assess the clinical efficacy and patient compliance after dental health education of interdental floss when used alongside toothbrushing for dental plaque control. Materials and Methods: A prospective observational comparative study was conducted, involving 52 participants randomly divided into toothbrush and dental floss (TB + DF) and toothbrush (TB) groups. The participants underwent professional prophylaxis, and interdental floss education was provided to the TB + DF group. Results: Results showed significant differences between the groups at 7 days and 1 month, favoring the floss group in terms of approximal plaque index. However, the toothbrush group exhibited better outcomes for interdental bleeding at 7 days. Patients’ perceptions of cleaning capacity, comfort, and Visual Analog Scale scores were also evaluated. While no significant difference was observed in cleaning capacity perception at 7 days, the floss group showed significantly better results at 1 month. Comfort favored the floss group at both time points. Conclusion: This study highlights the importance of dental health education in improving compliance and underscores the efficacy of interdental floss in conjunction with toothbrushing for comprehensive plaque control.